2020
DOI: 10.3390/ph13100292
|View full text |Cite
|
Sign up to set email alerts
|

Role of Protein Kinase CK2 in Aberrant Lipid Metabolism in Cancer

Abstract: Uncontrolled proliferation is a feature defining cancer and it is linked to the ability of cancer cells to effectively adapt their metabolic needs in response to a harsh tumor environment. Metabolic reprogramming is considered a hallmark of cancer and includes increased glucose uptake and processing, and increased glutamine utilization, but also the deregulation of lipid and cholesterol-associated signal transduction, as highlighted in recent years. In the first part of the review, we will (i) provide an overv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 224 publications
3
13
0
Order By: Relevance
“…The same analysis, using BP terms enriched following treatment with CX-4945 alone, showed the presence of the same two major functional modules (Supplementary Figure S8A). In agreement, CK2 inhibition has already been shown to affect the cell cycle, metabolism and mitochondrial functions [40,[89][90][91]. Furthermore, a comparison of the levels of deregulation of the major biological processes, defined by the Normalized Enriched Score (NES), showed that they were overall more deregulated in the KU-60019/CX-4945 condition than with CX-4945 alone (Supplementary Figure S6E).…”
Section: Ku-60019/cx-4945 Combination Leads To a Stronger Transcriptome Deregulation Than The Drugs Alonesupporting
confidence: 67%
“…The same analysis, using BP terms enriched following treatment with CX-4945 alone, showed the presence of the same two major functional modules (Supplementary Figure S8A). In agreement, CK2 inhibition has already been shown to affect the cell cycle, metabolism and mitochondrial functions [40,[89][90][91]. Furthermore, a comparison of the levels of deregulation of the major biological processes, defined by the Normalized Enriched Score (NES), showed that they were overall more deregulated in the KU-60019/CX-4945 condition than with CX-4945 alone (Supplementary Figure S6E).…”
Section: Ku-60019/cx-4945 Combination Leads To a Stronger Transcriptome Deregulation Than The Drugs Alonesupporting
confidence: 67%
“…The CK2 implication in cancer energetics can be also inferred by its regulatory role on Akt and its effectors mTORC1 and β-catenin [ 17 , 18 ], ultimately affecting the modulation of key metabolic targets, as recently described [ 19 ]. Moreover, CK2 plays a role in adipocyte metabolism [ 20 ], and its possible implication in cancer aberrant lipid metabolism has been hypothesized [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Increased cancer cell proliferation requires the rapid synthesis of lipids for the generation of biological membranes and lipid provide cancer cells with energy during times of nutrient depletion, lipids are also important signalling molecules. [2,5] The synthesis of lipids in healthy organisms is tightly controlled and responds to the nutrient's status of the cell. However, many human cancers display aberrant lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…However, many human cancers display aberrant lipid metabolism. [5] Next generation sequencing capabilities are revolutionizing approaches to all elds of medicine,recent advances in our understanding of tumor biology have uncovered a growing list of clinically relevant biomarkers. [6] However, the vast majority of studies have concentrated mainly on a single gene, and its predictive ability is insu cient compared with multiple biomarker-based models.…”
Section: Introductionmentioning
confidence: 99%